Acute kidney injury due to multiple bee stings in a 3 years old girl - Omega Mellyana; Dessy Adelina; Jati Kusuma (RSUP Dr. Kariadi, 2019)
Background: Bee stings can lead to mild to severe allergic reaction . Serious complications of bee stings include hypersensitivity to the venom, which can develop after a single sting, and acute renal failure which has been reported mostly secondary of intravascular hemolysis developing after multiple bee stings. We report here a child who developed multiorgan system involvement. Case presentation: A-3 years-old-girl was admitted to Kariadi Hospital with multiple bee stings and referred due to acute kidney injury stage failure by local hospital. Clinical finding were anasarca edema, gastrointestinal bleeding, oliguria (0.8ml/kgBW/hours), stage II hypertension (124/99mmHg), flaccid paraparesis inferior. Laboratory finding were hypoalbuminemia (2.4g/dL), anemia (6g/dl), leukocytosis (35.800/mm3), electrolyte imbalance (hypocalsemia:1.66mg/dL) and estimated glomerular filtration rate (eGFR) 8.09 ml/min/1.73m2. Chest-X ray showed pulmonary edema and duplex pleural effusion. The renal function recovered with supportive management including four sessions of haemodialysis. Patient discharged from the hospital on the nineteenth day. Conclusions: Multiple bee stings can lead multiorgan system involvement Keyword: Bee sting, acute kidney injury, hemodialisys